The dynamics of trade variety and economic performance of ASEAN-5 - Mat Ghani, Gairuzazmi; Sofyan, Joel Farouk; Duasa, Jarita (2010)
ASEAN-5 (Indonesia, Malaysia, Philippines, Singapore, and Thailand) exports have been growing rapidly over the last decades. However, the growth may negatively affect welfare if it is followed by deterioration in the terms of trade, as implied by the standard Armington trade model. But the expansion of the variety of products exported may thwart the adverse terms of trade effect. Another important characteristic of ASEAN-5 exports is the heavy reliance on imported intermediate components, and hence the changes in imports may also affect exports and economic performance. This study measures the dynamics of export and import variety for the ASEAN-5 countries, for the period 1991–2007, using indexes which are based on the Shannon’s entropy. The study determines whether expansion in export and import variety, if any, has helped in improving exports and economic performance. We show that the dynamics of export and import variety for the ASEAN-5 countries are different. To examine the contribution of export and import variety on the growth of exports and economic performance, we augment the indexes of trade variety to the standard export function, and show that unrelated variety negatively affect export, and related variety (RV) of imported products positively affect export growth.